(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the surface changes of glass ceramics, submitted to artificial aging by simulated brushing with different toothpastes, using a brushing machine designed by the authors. Twenty-four specimens were made in the form of an upper right central incisor, in color A1 and made up in color A3; divided into 4 groups with n =6. The mechanical tests were performed by a brushing machine at an ambient temperature of 37ºC, with a frequency of 250 strokes per minute, under 250mg brush pressure and simultaneous dripping of the dentifrice solution. Test times were divided into: 0; 25,000; 50,000; 75,000; 100,000; 125,000 and 150,000 strokes and the parameters analyzed by a rugosimeter. The obtained values of surface roughness (SR) were submitted to the Kolmogorov-Smirnov test (p=0.321) to verify the normality of the data distribution and, later, to the Levene test (p=0.076). The results obtained showed that the aging time did not influence the surface roughness of the glass ceramics, there were differences in surface roughness in some toothpastes. Thus, it can be concluded that the glass ceramics were susceptible to mass loss, but resistant to the action of toothpastes. Dentifrices with anti-plaque and anti-tartar characteristics can change the surface over time.